The Effects of Ultra-High Pressure Combined with Egg White Protein on the Gel Physical Properties of Reduced-Salt Shrimp Surimi - Yefan Wang; Zisheng Zhai; Xinchi Yu; Deyang Li (Foods, 2025)
This study investigated the synergistic effects of ultra-high pressure (UHP) and egg white protein (EWP) on the gel properties of sodium-reduced shrimp surimi. A Box–Behnken design targeting UHP pressure (200–400 MPa), duration (10–20 min), and EWP/myofibrillar protein (MP) ratio (1:9–5:5) was implemented to optimize gel strength, water holding capacity (WHC), and whiteness. Optimal conditions (290 MPa/15 min/EWP:MP = 3:5) yielded the following validated improvements, versus conventional processing: 282.27 g·mm gel strength, 14.90% WHC enhancement, and 16.63% reduced cooking loss. Texture profile analysis demonstrated superior elasticity in composite gels. Magnetic resonance imaging and scanning electron microscopy revealed a denser microstructure with enhanced water-binding capacity, corroborated by the rheological evidence of strengthened viscoelasticity. UHP promotes the partial expansion of MP, exposing hydrophobic groups and sulfhydryl groups, thereby enhancing intermolecular interactions. It also promotes the expansion of EWP, enabling the formation of disulfide bonds between molecules and facilitating the formation of network structures. These findings propose a scalable strategy for developing clean-label salt-reduced aquatic surimi products.